The Dual Roles of the Government Budget and the Balance of Payments in the Movement From Short-Run to Long-Run Equilibrium - Branson, William H. (Quarterly Journal of Economics, 1976)
I. Introduction and background, 346.—II. A two-asset model with trade, 349.—III. Instantaneous equilibrium with a flexible exchange rate, 355.—IV. Stock equilibrium with a flexible exchange rate, 357.—V. Monetary and fiscal policy reconsidered, 361.—VI. Stock equilibrium with a fixed exchange rate, 364.—Appendix: Determinant condition for stock equilibrium, 366.